Malassezia spp. dan Peranannya sebagai Penyebab Dermatitis pada Hewan Peliharaan (MALASSEZIA SPP AND ITS ROLE AS THE CAUSAL AGENT OF DERMATITIS IN PET ANIMALS) - Adiyati, Pradipta Nuri; Pribadi, Eko Sugeng (Jurnal Veteriner, 2015)
Malassezia is dimorphic yeast found normally in the animal healthy skin. Malassezia can causehealth problem in pet animals, such as dogs, cats, and other domestic animals. Varies according itsvirulence, Malassezia can cause skin changes characterized by severe pruritus, yellowish erythema andscab, greasy skin, bad odor with hyperpigmentation and lichenification in the face, paws, and neck bottom,as well as belly. Laboratory diagnosis can be performed either by microscopic examination of nativepreparations, or molecular biology. Treatment of Malassezia’s infection can still be made using someantifungals currently available. Malassezia pachydermatitis infection has been known as zoonoticpotential.
Keywords: Malassezia, skin infection, pets